2021
DOI: 10.3390/ijms22052479
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evidence on Augmented Antiallodynia Following Systemic Co-Treatment with GlyT-1 and GlyT-2 Inhibitors in Rat Neuropathic Pain Model

Abstract: The limited effect of current medications on neuropathic pain (NP) has initiated large efforts to develop effective treatments. Animal studies showed that glycine transporter (GlyT) inhibitors are promising analgesics in NP, though concerns regarding adverse effects were raised. We aimed to study NFPS and Org-25543, GlyT-1 and GlyT-2 inhibitors, respectively and their combination in rat mononeuropathic pain evoked by partial sciatic nerve ligation. Cerebrospinal fluid (CSF) glycine content was also determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…12 Consistently, a recent study found that increasing cerebrospinal fluid glycine content by applying glycine transporter inhibitors results in an obvious antiallodynic effect in a rat model of neuropathic pain, indicating an important role for glycine in the regulation of mechanical allodynia. 33,34 Activation of ErbB4 by NRG1 has been shown to increase AMPAR endocytosis in hippocampal neurons. 20 Furthermore, previous studies have indicated that AMPAR endocytosis-mediated long-term depression is involved in spinal glycinergic neuron-mediated disinhibition.…”
Section: Discussionmentioning
confidence: 99%
“…12 Consistently, a recent study found that increasing cerebrospinal fluid glycine content by applying glycine transporter inhibitors results in an obvious antiallodynic effect in a rat model of neuropathic pain, indicating an important role for glycine in the regulation of mechanical allodynia. 33,34 Activation of ErbB4 by NRG1 has been shown to increase AMPAR endocytosis in hippocampal neurons. 20 Furthermore, previous studies have indicated that AMPAR endocytosis-mediated long-term depression is involved in spinal glycinergic neuron-mediated disinhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, in cases of acute or inflammatory pain types, opioid analgesics can provide adequate pain control, which is somewhat hampered by above mentioned unwanted effects. However, in the case of neuropathic pain, the desired analgesia itself is often unachievable, consequently demanding dose-escalation, therefore causing more pronounced side effects (Figure 1A) (Karádi and Al-Khrasani, unpublished data) and (Figure 1B) (adopted from our previous work [16]). In each treatment group, 4-7 animals were used.…”
Section: The Opioid System and The µ-Opioid Receptor In Different Pain Entitiesmentioning
confidence: 99%
“…In each treatment group, 4-7 animals were used. These results were adopted from our previous work [16].…”
Section: The Opioid System and The µ-Opioid Receptor In Different Pain Entitiesmentioning
confidence: 99%
See 2 more Smart Citations